CAD/CAM SYSTEMS AS THE CORE OF MODERN ENGINEERING: CHALLENGES AND SOLUTIONS ON THE SHOP FLOOR - Rodrigues, Bruno Martimiaano (LUMEN ET VIRTUS, 2023)
The integration of Computer-Aided Design (CAD) and Computer-Aided Manufacturing (CAM) systems has become a foundational element of modern engineering practice in the United States, enabling high-precision manufacturing, process optimization, and smart factory development. This article examines the strategic role of CAD/CAM platforms—particularly SolidWorks and PowerMill—in bridging the gap between digital design and physical production on the American factory floor. It explores the challenges faced by U.S. manufacturers, such as workforce skill shortages and technology implementation barriers, while highlighting practical solutions adopted in both domestic and international contexts. Emphasis is placed on the value of professionals with hands-on experience in emerging markets like Brazil, where adaptive use of CAD/CAM tools under resource constraints offers transferable insights for American industry. The discussion also connects CAD/CAM integration to Industry 4.0 principles, underscoring its significance for productivity, agility, and long-term competitiveness.